Popular vs. Professional Aspects of Economics Texts in English - Brekke, Magnar (HERMES - Journal of Language and Communication in Business, 1999)
This article takes up the important issue of distinguishing popular from professional texts using economic texts as the object of analysis. It reports on a limited corpus study of authentic texts produced by native English professionals and published for na-tive English readers, but differing in the nature of intended audience (lay/expert). Economics/electronic money transactions constituted the textual domain/subdomain, and the dominant text type was expository. Following a basic quantitative check and a tentative readability ranking the text samples were scrutinized with respect to lexical profile, frequency band penetration, terminological density and uniqueness. A detailed collocation study was then made of focal multi-word terms as well as personal pronouns. Standard corpus techniques were employed in exposing regularities and produ-cing supporting documentation. At the same time possible reflections of communicative situation, pragmatic purpose and semiotic significance were noted. An attempt was then made to integrate such internal (“linguistic”) and external (“situational”) var-iables as revealed by a comprehensive textual analysis in a synopsis intended to bring out a possible clustering of features. The general question to which an answer was sought was to what extent is each perspective necessary and/or sufficient in defining the textual genre?